2021
DOI: 10.1155/2021/4340950
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Promotes Apoptosis and Restrains the Viability and Migration of Bladder Cancer by Impeding TRPM7 Expression via the ERK and AKT Signaling Pathways

Abstract: Background. Oridonin is a powerful anticancer compound found in Rabdosia rubescens. However, its potential impact on bladder cancer remains uninvestigated. In this work, we aimed to detect the anticancer effect of oridonin on bladder cancer and explore the molecular mechanisms involved. Methods. The anticancer activity of oridonin was assessed in vitro with a CCK8 assay, an annexin V-FITC apoptosis analysis, and colony formation and Transwell migration assays which were performed with the human bladder cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…ORI can induce retardation of the cancer growth and apoptosis of human cancer cells by promoting p53 expression and activity (Ikezoe et al, 2003). ORI also modulates the PI3K/AKT pathway, TGFβ pathway, and cell death pathways to exert its anticancer influence (Bu et al, 2019;Che et al, 2021;Han et al, 2020) Abbreviations: Bcl-2, B-cell lymphoma 2; BAX, Bcl-2-associated X protein; EGFR, Epidermal growth factor receptor; ERK, extracellular signal-regulated kinase; p53, tumor protein p53; JNK, Jun N-terminal kinase; MAPK, mitogen-activated protein kinase; β1/FAK, integrin-focal adhesion kinase; MDM2, murine double minute 2; FGFR3, fibroblast growth factor receptor 3; NF-κβ, Nuclear factor kappa B; PI3K, phosphoinositide-3-kinase protein kinase; RAF, rapidly accelerated fibrosarcoma.…”
Section: Ori Ac Tivit Y In D Ifferent C An Cer S In Vitro S Tud Ie Smentioning
confidence: 99%
See 1 more Smart Citation
“…ORI can induce retardation of the cancer growth and apoptosis of human cancer cells by promoting p53 expression and activity (Ikezoe et al, 2003). ORI also modulates the PI3K/AKT pathway, TGFβ pathway, and cell death pathways to exert its anticancer influence (Bu et al, 2019;Che et al, 2021;Han et al, 2020) Abbreviations: Bcl-2, B-cell lymphoma 2; BAX, Bcl-2-associated X protein; EGFR, Epidermal growth factor receptor; ERK, extracellular signal-regulated kinase; p53, tumor protein p53; JNK, Jun N-terminal kinase; MAPK, mitogen-activated protein kinase; β1/FAK, integrin-focal adhesion kinase; MDM2, murine double minute 2; FGFR3, fibroblast growth factor receptor 3; NF-κβ, Nuclear factor kappa B; PI3K, phosphoinositide-3-kinase protein kinase; RAF, rapidly accelerated fibrosarcoma.…”
Section: Ori Ac Tivit Y In D Ifferent C An Cer S In Vitro S Tud Ie Smentioning
confidence: 99%
“…In a GBC-SD cell xenograft model, ORI also inhibited cell growth and reduced HIF-1 and MMP-9 expression levels. Notably, ORI targets the HIF-1/MMP-9 signaling pathway to inhibit tumor cell motility and EMT(Chen et al, 2019).Similarly, sorafenib and ORI when combined, synergistically suppressed proliferation, invasion, migration, and EMT while inducing apoptosis by altering the AKT pathway without affecting NFκβ or MAPK signaling(Chen et al, 2019).Likewise, ORI inhibited T24 cells' ability to proliferate, form colonies, and migrate by dramatically upregulating p53 and cleaved caspase-3 expression levels while downregulating transient receptor potential cation channel subfamily M member 7, phosphorylated AKT (p-AKT), and phosphorylation of ERK (p-ERK) expression(Che et al, 2021).…”
mentioning
confidence: 99%
“…Different works related TRPM7 upregulation to bladder cancer (Bca) cells’ proliferation, motility, and apoptosis ( 200 , 201 , 306 ). TRPM7 knockdown reduced the migration and invasion ability of UMUC3 and T24 cells by suppression of JNK (c-Jun N-terminal kinase), Akt, and Src phosphorylation.…”
Section: Trpm Channels: Characteristics and Functionsmentioning
confidence: 99%
“…Treatment with carvacrol inhibited TRPM7 activity and restricted the tumor size in a xenograft model ( 201 ; Table 1 ). Another TRPM7 inhibitor, oridonin, suppressed the proliferative activity, as well as colony-formation and migration capacities of T24 cells, eliciting wide-ranging apoptosis in vitro , and delayed tumor growth in vivo ( 200 ; Table 1 ). On the other hand, treatment with oridonin appreciably improved p53 expression levels, increased caspase-3 activity, and reduced the expression of p-AKT, p-ERK, and TRPM7 channels.…”
Section: Trpm Channels: Characteristics and Functionsmentioning
confidence: 99%
“…The antitumor activity of oridonin has been widely studied. Oridonin can effectively inhibit viability of a variety of tumor cells, mainly by inhibiting cancer cell proliferation, promoting apoptosis, but also triggering autophagy [ 9 , 10 ]. Yang and others confirmed that oridonin has antilung cancer pharmacological activity through inhibition of AMPK/Akt/mTOR-dependent autophagy and reduced cisplatin resistance through activation of apoptosis signaling pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%